Ukrainian Language as a Means of Unification of Society and a Factor of National Security of Ukraine - Kravchenko, Liudmyla (Ukrainian linguistics, 2022)
The article highlights the leading role of language in the formation of society through the analysis of its main functions, namely: communication, impact on a person, consolidation of citizens, the formation of national identity. This work analyses the relationship between the change of the language policy vector in Ukraine towards Ukrainian centricity and the strengthening of the Ukrainian language functioning  in various spheres.The article raises the issue of the role of language as one of the important factors of national security of Ukraine. The role of the language issue in the Russian occupation of a part of Ukraine as a result of a hybrid war is exemplified. An integral part of this hybrid war is a change in worldview and a change in the national code of the inhabitants of the occupied territories.Based on our sociolinguistic opinion poll of 230 military officers of the Armed Forces of Ukraine, conducted in 2019, it was specified that among a number of markers of national identity, officers chose a common language. 54 % of respondents gave five points out of five possible to the marker of “common language”, and 20 % gave it four points. 88 % of respondents called the Ukrainian language as one of the main unifying tools in the formation of civil society in Ukraine, and 94,5 % believed that only the Ukrainian language should be the state language in Ukraine. It is important that military officers, born in different parts of Ukraine (and some far beyond its borders) and currently serving in different regions of the country, took part in the opinion poll. It allows us to affirm that officers understand the role of the Ukrainian language as a nation-building factor that is able to unite people in order to defend their country. Information about the author:Liudmyla Kravchenko – PhD, Associate Prof. of the Department of the Ukrainian Language and Applied Linguistics; Educational and Scientific Institute of Philology; Taras Shevchenko National University of Kyiv (Ukraine).(Ukraine).E-mail: lutwins@ukr.net__________References• Azhniuk B. M. (2021). Language politics: Ukraine and the world: monograph. Kyiv: Vydavnychyi dim Dmytra Buraho, 420 p. (in Ukrainian).• Voropai O. (1958). Customs of our people. Ethnographic sketch. Рart. І. Munich, 455 p. (in Ukrainian).• Hybrid war: technologies of suggestion and counter suggestion (2018). Kyiv, National academy of SBU, 235 p. (in Ukrainian).• Hrechka S. O. (2018). “Cultural weapon” as a component of consciental war against Ukraine. Movni i konceptualni kartyny svitu. Issue 2(64). Kyiv: VPC “Kyivskyj universytet”, pp. 53–58 (in Ukrainian).• Zalizniak H. (2010). Ukrainians’ language orientations and their civilizational choice. Language politics and language situation in Ukraine: analysis and recommendations, Yu. Besters-Dilger (ed.), Kyiv: Vydavnychyi dim “Kyiv Mohyla Academy”, pp. 132–166 (in Ukrainian).• Masenko L. (2010). Sketches in sociolinguistics. Kyiv: Vydavnychyi dim “Kyiv Mohyla Academy”, 243 p. (in Ukrainian).• Masenko L. (2007). (U)movna (U)krayina. Kyiv: Tempora, 88 p. (in Ukrainian).• Matveieva N. R.(2021). Ukrainian-Russian bilingualism and diglossia in Kyiv modern communicative space. Qualification scientific work on the manuscript rights. Ternopil–Kyiv, 239 p. (in Ukrainian).• Language legislation and language politics: Ukraine, Europe, the world (Collection of scholarly articles) (2019). Kyiv: Vydavnychyi dim Dmytra Buraho, 688 p. (in Ukrainian).• Petriv K. V. (2019). The Conceptosphere of National Identity and its Language Objectivation in Oksana Pakhlovska’s Social and Political Essays. A qualifying scientific work manuscript. Thesis submitted for Candidate Degree in Philology. Kyiv, 312 p. (in Ukrainian).• Selivanova O. (2008). Modern linguistics: directions and problems. Poltava: Dovkillia-K, 712 p. (in Ukrainian).• Skorohod O. (2014). Oleh Skrypka: Territories, where the Ukrainian language was almost forbidden, are either occupied, or covered with blood of the war. Portal movnoyi polityky.17, December, 2014. URL: http://language-policy.info/2014/12/17/ (accessional date: 10.03.2021) (in Ukrainian).• Stepanenko M. (2015). The Ukrainian language and social and political transformations of the present. Ukrainska mova, № 2, pp. 7–23 (in Ukrainian).• Sheveliov Y. (1998). The Ukrainian Language in the First Half of the Twentieth Century (1900–1941): its state and status. Chernivtsi: “Ruta”, 208 p. (in Ukrainian).• Roslycky Lada(2015). Language, psychological war, national security. Mova i suspilstvo. Issue 6, pp. 3–22.
Keywords: language policy, language situation, state language, national identity, national security, language status planning, language corpus planning